Produção de biodiesel a partir de óleo de coco (Cocos nucifera L - Araújo, Giselle de Souza (2008)
The production of biodiesel has become an important and attractive process for the production of alternative fuels. This work presents a study of the biodiesel production from coconut oil (Cocos nucifera L.), by two routes: direct transesterification using NaOH as catalyst and esterification (with H2SO4) followed by basic transesterification. The reactor was built in pirex with 1L of capacity and was equipped with a jacket coupled with a thermostatic bath to temperature control, a mecanical stirring is also present in the reactor. The analysis of oil composition was carried out by gas chromatography and esters compounds were identified. The parameters of molar ratio oil/alcohol, reaction time and temperature were studied and their influence on the conversion products was evaluated using experimental planning (23). The molar ratio was the most significant variable by the statistical planning analysis. Conversions up to 85.3% where achived in the esterification/transesterification, with molar ratio 1:6 at 60ºC and 90 minutes of reaction. For the direct transesterification, route conversions up 87.4% eas obtained using 1:6.5 molar ratio at 80ºC and 60 minutes of reaction. The Coconut oil was characterized by their physic chemical properties and key constituents of the oil. The lauric acid was the main constituint and the oil showed high acidity. The biodiesel produced was characterized by its main physicochemical properties, indicating satisfactory results when compared to standard values of National Petroleum Agency. The work was supplemented with a preliminary assessment of the reaction kinetic